Principles of Entrepreneurship (ENT530): Business Model Canvas: Rörlig Iron Board / Muhammad Adli Izar Zaimi … [et al.] - Zaimi, Muhammad Adli Izar; Abdullah, Nurin Jazlina; Abdul Halim, Nur Syafika; Mohamad, Nurul Asyiqin; Azamudin, Nur Munirah (2021)
The Business Model Canvas (BMC) is being used in the report as a strategic management function to rapidly and simply develop and express business ideas and concepts. In this topic, we can learn how to prepare a business, how to distribute information, how to ensure that others are aware of our business and what we will receive once it is able to run. Simultaneously, we learn how to be successful entrepreneurs. Before starting a business, we need to identify nine aspects in the Business Model Canvas (BMC). It is due to the fact that the parts of BMC are designed to generate successful business. We find a possible target market that might be interested in purchasing our product. We also establish a market distribution channel to ensure that the products are available to the customer. We also identify the costs of manufacturing and determine the company's partners and suppliers. MANAS Sdn. Bhd. is a start up company with 5 members. We decided to enter the manufacturing business since we are interested in it and have some understanding of it. Our company's initial product is an iron board called Rörlig Iron Board. We want to overcome the issues associated with standard iron boards by creating a foldable iron board and attaching a holder to make it easy to transport anywhere. It would not take up much space due to its foldability since it can be folded after using or while packing. Furthermore, we make it lightweight by using lighter metal to make it lighter than a standard board. The aim behind this folding iron board is to help travelers and students by putting ourselves in their shoes and identifying issues. As a result, this concept may assist in resolving difficulties, facilitating everyone, particularly students and travelers, and providing complete pleasure with our product.